"y'+2ty=4t^3"
Multiply both parts of the equation by "e^{t^2}":
"e^{t^2}y'+2te^{t^2}y=4t^3e^{t^2}"
"(e^{t^2}y)'=4t^3e^{t^2}"
"e^{t^2}y=4\\int t^3e^{t^2}dt=2\\int t^2e^{t^2}dt^2="
"\\ \\ \\ \\ \\ |t^2=x|"
"=2\\int xe^{x}dx="
"\\ \\ \\ \\ \\ |u=x, dv=e^xdx, du=dx, v=e^x|"
"=2xe^x-2\\int e^xdx+C=2xe^x-2e^x+C="
"\\ \\ \\ \\ |x=t^2|"
"=2e^{t^2}(t^2-1)+C"
Therefore, we have the following equation:
"e^{t^2}y=2e^{t^2}(t^2-1)+C"
Finally, the general solution of the differential equation is the following:
"y=2(t^2-1)+Ce^{-t^2}"
Comments
Leave a comment